Digital signal processing : signals systems and filters - Andreas Antoniou (Chennai McGraw Hill Education India Pvt Ltd, 2017)
An up-to-the-minute textbook for junior/senior level signal processing courses and senior/graduate level digital filter design courses, this text is supported by a DSP software package known as D-Filter which would enable students to interactively learn the fundamentals of DSP and digital-filter design. The book includes a free license to D-Filter which will enable the owner of the book to download and install the most recent version of the software as well as future updates.
Keywords: Signal Processing; Digital Techniques